NF-kappa B sites function as positive regulators of expression of the translocated c-myc allele in Burkitt's lymphoma. - Ji, L (1994)
An in vivo footprint over a potential NF-kappa B site in the first exon of the c-myc gene has been identified on the translocated allele in the Ramos Burkitt's lymphoma cell line. The potential NF-kappa B site in the 5' flanking sequence of c-myc was found to be occupied on the translocated allele in the Raji Burkitt's cell line. Electrophoretic mobility shift assays with each of these sequences demonstrated complexes with mobilities identical to those of the NF-kappa B site from the kappa light-chain gene. A supershift was obtained with anti-p50 antibody with the exon site. The upstream-site shift complex disappeared with the addition of anti-p50 antibody. Binding of NF-kappa B proteins to the c-myc exon and upstream sites was demonstrated by induction of binding upon differentiation of pre-B 70Z/3 cells to B cells. UV cross-linking experiments revealed that a protein with a molecular mass of 50 kDa bound to the exon and upstream sites. Transfection experiments with Raji cells demonstrated that both sites functioned as positive regulatory regions, with a drop in activity level when either site was mutated. Access to these sites is blocked in the silent normal c-myc allele in Burkitt's lymphoma cells, while Rel family proteins bind to these sites in the translocated allele. We conclude that the two NF-kappa B sites function as positive regulatory regions for the translocated c-myc gene in Burkitt's lymphoma.